Osteopontin deficiency ameliorates Alport pathology by preventing tubular metabolic deficits - Ding, Wen (JCI Insight, 2018)
Alport syndrome is a rare hereditary renal disorder with no etiologic therapy. We found that osteopontin (OPN) is highly expressed in the renal tubules of the Alport mouse and plays a causative pathological role. OPN genetic deletion ameliorated albuminuria, hypertension, tubulointerstitial proliferation, renal apoptosis, and hearing and visual deficits in the Alport mouse. In Alport renal tubules we found extensive cholesterol accumulation and increased protein expression of dynamin-3 (DNM3) and LDL receptor (LDLR) in addition to dysmorphic mitochondria with defective bioenergetics. Increased pathological cholesterol influx was confirmed by a remarkably increased uptake of injected DiI-LDL cholesterol by Alport renal tubules, and by the improved lifespan of the Alport mice when crossed with the Ldlr(–/–) mice with defective cholesterol influx. Moreover, OPN-deficient Alport mice demonstrated significant reduction of DNM3 and LDLR expression. In human renal epithelial cells, overexpressing DNM3 resulted in elevated LDLR protein expression and defective mitochondrial respiration. Our results suggest a potentially new pathway in Alport pathology where tubular OPN causes DNM3- and LDLR-mediated enhanced cholesterol influx and impaired mitochondrial respiration.